A first empirical analysis of population stability in North America using radiocarbon records. (September 2020) - Bird, Darcy; Freeman, Jacob; Robinson, Erick; Maughan, Gideon; Finley, Judson Byrd; Lambert, Patricia M; Kelly, Robert L
Questions regarding population stability among animals and plants are fundamental to population ecology, yet this has not been a topic studied by archeologists focusing on prehistoric human populations. This is an important knowledge gap. The fluctuation of human populations over decades to centuries – population instability – may constrain the expansion of human economies. A first step toward describing basic patterns of population stability would be to identify sizes of fluctuations through time, since smaller fluctuations are more stable than larger fluctuations. We conduct a biogeographic analysis of the long-term stability of human societies in North America using a continental scale radiocarbon dataset. Our analysis compares the stability of summed calibrated radiocarbon date probability distributions (SPDs) with subsistence strategies and modeled climate stability between 6000 and 300 BP. This coarse-grained analysis reveals general trends regarding the stability of human systems in North America that future studies may build upon. Our results demonstrate that agricultural sequences have more stable SPDs than hunter-gatherer sequences in general, but agricultural sequences also experience rare, extreme increases and decreases in SPDs not seen among hunter-gatherers. We propose that the adoption of agriculture has the unintended consequence of increasing population density and stability over most time scales, but also increases the vulnerability of populations to large, rare changes. Conversely, hunter-gatherer systems remain flexible and less vulnerable to large population changes. Climate stability may have an indirect effect on long-term population stability, and climate shocks may be buffered by other aspects of subsistence strategies prior to affecting human demography.